Myocardial inflammation comes of age. Issue 19 (February 2021) - Appel, Marc; Frantz, Stefan; Campos Ramos, Gustavo
Highlights: Aging is a major risk factor for heart diseases, and the elderly population has steadily increased worldwide. The heart and immune system undergo significant alterations with age, which impact the progression of heart diseases. Aging is an inevitable process, but the pace and intensity at which immunosenescence progresses can vary among subjects. Assessing the immunosenescence status in heart disease patients might offer valuable diagnostic and prognostic information. Abstract : Life expectancy has steadily increased over the past century, as has the occurrence of age-related diseases, most notably myocardial diseases. Aging is often accompanied by increased low-grade chronic inflammation, accumulation of terminally differentiated T-cells poised with proinflammatory phenotypes, and clonal hematopoiesis. These systemic alterations have been consistently shown to impact myocardial physiology, individual susceptibility to heart diseases and long-term heart disease prognosis. In recent years, progress has been made in understanding the interindividual (cross-sectional) and intraindividual (longitudinal) variability in the global immunosenescence profile, and novel immune-aging metric-based scoring systems bearing potential to predict cardiovascular events have emerged. We herein suggest that monitoring the patients' individual immunosenescence trajectories, in addition to the classic cardiological work-up, could provide valuable diagnostic/prognostic information. Similarly, we propose that basic research in cardio-immunology could attain a deeper mechanistic understanding of age-related diseases and a more meaningful translational impact if the 'aging context' was embraced more systematically.